Seed-mediated plasmon-driven regrowth of silver NanoDecahedrons (NDs) - Lu, Haifei (2013)
We report the synthesis of silver nanodecahedrons (NDs) for extending the localized surface plasmon resonance (LSPR) of silver nanostructures from blue to green-orange (~590 nm), which will enable much wider application opportunities using common laser light sources. In our photo-assisted method, we use a light-emitting-diode (LED) to control regrowth of silver ND from precursor seeds. Highly uniform silver NDs are synthesized when the LED emission peak coincides with the LSPR peak of the seeds. A two-step process involving precursor self-transformation into silver nanoprisms and nanoplates, and subsequent photo-activated regrowth of silver NDs has been proposed. Surface-enhanced Raman scattering of silver NDs in different sizes has been studied, and the average enhancement factor for each size is estimated to be in the order of ~10^6.